2022
DOI: 10.3389/fpubh.2022.1023176
|View full text |Cite
|
Sign up to set email alerts
|

A topology-based evaluation of resilience on urban road networks against epidemic spread: Implications for COVID-19 responses

Abstract: Road closure is an effective measure to reduce mobility and prevent the spread of an epidemic in severe public health crises. For instance, during the peak waves of the global COVID-19 pandemic, many countries implemented road closure policies, such as the traffic-calming strategy in the UK. However, it is still not clear how such road closures, if used as a response to different modes of epidemic spreading, affect the resilient performance of large-scale road networks in terms of their efficiency and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Moreover, China has experienced increased economic downward pressure in recent years [78] with high unemployment; thus, livelihood issues must be addressed as well. Meanwhile, the impact of the global COVID-19 epidemic has led to a certain degree of spatial isolation in China [79], causing public anxiety, depression, and other mental health problems [2], [8], providing a contrasting pressure to the increasing public demand for tourism and leisure. Coupled with the fact that some problems [80], [81] have emerged during the implementation of new urbanization in China in recent years, such as the similarity of town development patterns and the loss of traditional culture [82], the National Development and Reform Commission of China has been exploring new paths for urbanization development, aiming to maintain sustainable and healthy economic development.…”
Section: A Background Of the Emergence Of Night Agglomeration Areas I...mentioning
confidence: 99%
“…Moreover, China has experienced increased economic downward pressure in recent years [78] with high unemployment; thus, livelihood issues must be addressed as well. Meanwhile, the impact of the global COVID-19 epidemic has led to a certain degree of spatial isolation in China [79], causing public anxiety, depression, and other mental health problems [2], [8], providing a contrasting pressure to the increasing public demand for tourism and leisure. Coupled with the fact that some problems [80], [81] have emerged during the implementation of new urbanization in China in recent years, such as the similarity of town development patterns and the loss of traditional culture [82], the National Development and Reform Commission of China has been exploring new paths for urbanization development, aiming to maintain sustainable and healthy economic development.…”
Section: A Background Of the Emergence Of Night Agglomeration Areas I...mentioning
confidence: 99%
“…Overall, the impact of COVID-19 on transportation is significant [34,35] and negative [36][37][38], which is agreed generally. Meanwhile, the existing research has also observed that (1) the impact of the pandemic on transport varies by region [39,40]; (2) external intervention in the prevention and control of the pandemic can produce positive temporal and spatial effects [3,6,41]. Among the studies on the impact of the COVID-19 pandemic on transport, the studies in the field of road transport are few, and the studies that have quantified the resilience of road transport to the COVID-19 pandemic are even fewer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth noting that this systematic literature review (SLR) only concentrates on the indirect effects of floods on transportation. However, if a broader range of disasters, such as the spread of epidemics [55], or a wider context of analysis, such as network resilience [56,57], is considered, it will be observed that more modes of transportation are included.…”
Section: Rq5 What Transportation Modes Are Evaluated In the Indirect ...mentioning
confidence: 99%